Pembuatan dan Aktivitas Anti-Acne Nano Essence Sheet Mask Ekstrak Bonggol Nanas (Ananas comosus (L.) Merr) - Ritonga , Nur Sakina; Lubis, Minda Sari; Yuniarti , Rafita; Rani , Zulmai (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Pineapple tubers, which are often considered waste, contain chemical compounds such as flavonoids, alkaloids, aPineapple tubers, which are often considered waste, contain chemical compounds such as flavonoids, alkaloids, saponins, tannins, and glycosides. This compound has antibacterial effects, especially against Propionibacterium acnes, which are gram-positive bacteria that cause acne. Anti-acne masks effectively prevent acne by disrupting the growth or killing bacteria through inhibiting microbial metabolism. This research is experimental in nature with Independent Variables: Extract, pineapple tuber simplicia, essence preparation, and nano essence sheet mask. Dependent variables include the physical characteristics of the preparation, as well as anti-acne activity. The extract was made using the maceration method, and then the antibacterial test of the extract was conducted. The preparations were subjected to physical quality tests, irritation tests, and antibacterial tests using the disc method. Orientation test results for the antibacterial activity of pineapple tuber extract against Propionibacterium acne s using the agar diffusion method with disc paper, namely, 3.25% (4.1 mm), 6.25% (4.9 mm), 12.5% (6.4 mm), 25% (7.5 mm), 50% (7.8 mm). The concentration of the preparation was obtained at 12.5% and then tested by PSA ( Particle Size Analyzer ). All particles were below 1000 nm, meeting the requirements. The results of the antibacterial activity test of the preparation showed the following inhibition zones: Blank (0 mm), Essence (9.5 mm), Nano Essence (11.13 mm), Comparator (25.3 mm), Clindamycin (32.3 mm). Good physical quality and can be used as an anti-acne.saponins, tannins and glycosides. This compound has antibacterial effects, especially against Propionibacterium acne s, gram-positive bacteria that cause acne. Anti- acne masks are effective in preventing acne by disrupting the growth or killing bacteria through inhibiting microbial metabolism. This research is experimental in nature with Independent Variables: Extract, pineapple tuber simplicia, essence preparation and nano essence sheet mask. Dependent variables include the physical characteristics of the preparation, as well as anti- acne activity . The extract was made using the maceration method, then the antibacterial test of the extract was oriented.The preparations were subjected to physical quality tests and irritation tests, as well as antibacterial tests using the disc method. Orientation test results for the antibacterial activity of pineapple tuber extract against Propionibacterium acne s using the agar diffusion method with disc paper, namely, 3.25% (4.1 mm), 6.25% (4.9 mm), 12.5% (6.4 mm), 25% (7.5 mm), 50% (7.8 mm). The concentration of the preparation was obtained at 12.5% and then tested by PSA ( Particle Size Analyzer ). All particles were below 1000 nm, meeting the requirements. The results of the antibacterial activity test of the preparation showed the following inhibition zones: Blank (0 mm), Essence (9.5 mm), Nano Essence (11.13 mm), Comparator (25.3 mm), Clindamycin (32.3 mm). Good physical quality and can be used as an anti -acne.